2005
DOI: 10.1889/1.2036349
|View full text |Cite
|
Sign up to set email alerts
|

59.4: Novel Device Structure of Field Effect — Ferroelectric Electron Emitter

Abstract: A novel micro structure of electron emitting portion has been developed for Field Effect -Ferroelectric Electron Emitter. This micro structure has numerous electron emitting micro-holes in high density. We have successfully improved luminance efficiency and emission angle dispersion by this micro structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recently, Ohwada and coworkers observed that a large number of electrons are emitted from the surface of a ferroelectric thick film having both a number of microopenings on the upper electrode and ''vacuum gaps'' between the upper electrode and the surface of the ferroelectric layer. [8][9][10][11] They also observed two types of electron emission. One was electron emission from the whole surface of the emitter during a positive polarization reversal, which was considered to be dark emission owing to the switch in surface polarization.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, Ohwada and coworkers observed that a large number of electrons are emitted from the surface of a ferroelectric thick film having both a number of microopenings on the upper electrode and ''vacuum gaps'' between the upper electrode and the surface of the ferroelectric layer. [8][9][10][11] They also observed two types of electron emission. One was electron emission from the whole surface of the emitter during a positive polarization reversal, which was considered to be dark emission owing to the switch in surface polarization.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, we developed an electron emitter in which an upper electrode with numerous micro-holes is arranged so as to not contact the ferroelectric surface, thus forming a vacuum gap. In 2004-2005, we used such an electron emitter to fabricate a prototype field emission display with diagonal size of 4.3 inches, and used it to render 128 gray-scale video [7,8]. However, the role of the vacuum gap in the electron emission mechanism remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004 and 2005, we published a novel ferroelectric electron emitter that has a unique microstructure of electron-emitting portions formed between the upper electrode and the surface of the ferroelectric layer. 7,8) By utilizing the ferroelectric emitters as subpixels, we demonstrated a moving colored image using 128 gray scales per color displayed on a 4.3-in. prototype fieldemission display.…”
Section: Introductionmentioning
confidence: 99%